2015
DOI: 10.1093/ntr/ntv003
|View full text |Cite
|
Sign up to set email alerts
|

Use of E-Cigarettes Among Current Smokers: Associations Among Reasons for Use, Quit Intentions, and Current Tobacco Use

Abstract: Introduction: Research has documented growing availability and use of e-cigarettes in the United States over the last decade. Methods: We conducted a national panel survey of current adult cigarette smokers to assess attitudes, beliefs, and behaviors relating to e-cigarette use in the United States (N = 2,254). Results: Among current cigarette smokers, 20.4% reported current use of e-cigarettes on some days and 3.7% reported daily use. Reported reasons for e-cigarette use included: quit smoking (58.4%), reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
173
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(193 citation statements)
references
References 30 publications
16
173
2
2
Order By: Relevance
“…Despite the fact that e-cigarettes have not been approved as a medication for smoking cessation by the Food and Drug Administration (FDA), they are widely promoted for smoking cessation, particularly to young adults, and smoking cessation is one of the main reasons that people try e-cigarettes. 6 Indeed, as of May 2016, no e-cigarette company had even submitted an application to the FDA to market e-cigarettes for smoking cessation.…”
Section: Do Not Recommend Trying E-cigarettes For Smoking Cessationmentioning
confidence: 99%
“…Despite the fact that e-cigarettes have not been approved as a medication for smoking cessation by the Food and Drug Administration (FDA), they are widely promoted for smoking cessation, particularly to young adults, and smoking cessation is one of the main reasons that people try e-cigarettes. 6 Indeed, as of May 2016, no e-cigarette company had even submitted an application to the FDA to market e-cigarettes for smoking cessation.…”
Section: Do Not Recommend Trying E-cigarettes For Smoking Cessationmentioning
confidence: 99%
“…Although not explicitly described in the context of being cool or uncool, some avoid EC use because they believe that EC users are old and addicted to nicotine 9 . Smokers may attempt cessation with ECs as a harmreduction strategy because of a common belief that ECs are healthier than cigarettes 4,[8][9][10][11] . The general population's beliefs fluctuate widely regarding the health effects of ECs compared to cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…The general population's beliefs fluctuate widely regarding the health effects of ECs compared to cigarettes. Studies have revealed that most believe that ECs are less harmful than cigarettes and even some believe that they are harmless [11][12][13][14] . Even when EC users have concerns about safety, there is a pervasive belief that ECs are a healthier alternative to cigarettes and that the harmful effects of cigarettes outweigh the consequences of EC use 12,15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations